2020
DOI: 10.3390/ma13071502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Thermal Stability and Surface Characteristics of Thermoplastic Polyurethane V-Belt

Abstract: This article proposes thermography as a non-contact diagnostic tool for assessing drive reliability. The application of this technique during the operation of the belt transmission with a heat-welded thermoplastic polyurethane V-belt was presented. The V-belt temperature changes depending on the braking torque load at different values of the rotational speed of the active pulley, which were adopted as diagnostic characteristics. In this paper, the surface morphology of the polyurethane (PU) belts was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…The tests of Wan et al from 2018 show that the glass transition of magnetorheological samples, manufactured on the basis of silicone rubber, at uniaxial compression occurs at the temperature of approximately 50 • C. The value of storage modulus points to two different trends, occurring along with temperature changes: at first it rapidly declines and then slightly increases, or maintains a constant value, as the temperature increases [22]. Systems that will use MRE can heat up as a result of heat radiating from co-operating devices, e.g., drive units [23], gearboxes [24], or working mechanisms [25]. Energy dissipation (resulting from regular operation) also increases the temperature of polymer materials, due to the occurrence of internal friction [26].…”
Section: Introductionmentioning
confidence: 99%
“…The tests of Wan et al from 2018 show that the glass transition of magnetorheological samples, manufactured on the basis of silicone rubber, at uniaxial compression occurs at the temperature of approximately 50 • C. The value of storage modulus points to two different trends, occurring along with temperature changes: at first it rapidly declines and then slightly increases, or maintains a constant value, as the temperature increases [22]. Systems that will use MRE can heat up as a result of heat radiating from co-operating devices, e.g., drive units [23], gearboxes [24], or working mechanisms [25]. Energy dissipation (resulting from regular operation) also increases the temperature of polymer materials, due to the occurrence of internal friction [26].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there is a need for improving or create novelty of the techniques of pulleys production, such as, e.g., additive methods as alternative techniques of producing non-circular pulleys-toothed wheels. The selection of the appropriate manufacturing technique has a significant impact on the geometrical parameters of the wheels as well as the durability and wear of the traction gear [ 5 , 6 ]. As well as in and load transfer technology, transport and control, it’s important to minimize the other errors such as, e.g., roundness error of the pulleys during the manufacturing stage for drive operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little up-to-date information regarding the effects of high temperature on this type of band and its resistance to combustion. During the transmission operation, the belts are exposed to high temperature as a result of damage to machine components or external factors 9 11 . For example, there may be a seizure and stoppage of the snub pulleys or intermediate pulleys, which change the nature of the interaction between the pulley and the belt from rolling to sliding friction 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Only V-belts, which are mainly used as transmission bands, not as conveyor belts, have been tested. Research has shown that these belts pose a serious threat to human life and health during a fire 10 , 11 . Therefore, it is necessary to try and use materials with relatively low impact on the environment to maintain the standards for the emission of harmful compounds described in documents and scientific works on fire protection 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%